Israel: Transport costs and customs duty - is on you The increase in customs value in Israel, due to the increase in transport prices – the problem, and the way to the solution - Wagner, Omer (The journal of contemporary issues in business and government, 2021)
In the past year, sea freight prices have risen sharply, an increase that has not been remembered for many years. Thus, according to various publications, about a year ago, renting a container for sea transportation from China to Israel, costed about 2,000$, and today, the same transportation costs about 15,000$. According to the publications, the reasons for this significant increase are due, among other things, to the COVID-19 crisis, global shortages of ships, declining competition in the field, and containers of contagious demand. In addition, there is a "Made of Israel" reason, since due to the congestion at ports in Israel, there are ships that prefer not to dock in Israel, and then the number of ships that can dock in Israel is even smaller2. Apart from the increase in transportation costs, which is expected to lead to a wave of price increases in the sale of products in Israel, there is another parameter that is slightly pushed to the margins, and that is the increase in the value of goods for customs purposes, due to rising transportation prices. This increase in prices leads to further collection of customs duties, purchase tax and import taxes, due to the increase in value. As I will present in this review, in my opinion - the Israeli law already allows the state to facilitate importers at this point - and similar and other facilitations have been made in the past. All that is required is the flexibility and activation of goodwill on the part of the state, when interpreting the law.